2021
DOI: 10.1021/acs.jchemed.1c00022
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Implementing Cloud-Based Tutorials That Combine Bioinformatics Software, Interactive Coding, and Visualization Exercises for Distance Learning on Structural Bioinformatics

Abstract: The COVID-19 pandemic has swiftly forced a change in learning strategies across educational institutions, from extensively relying on in-person activities toward online teaching. It is particularly difficult to adapt courses that depend on physical equipment to be now carried out remotely. This is the case for bioinformatics, which typically requires dedicated computer classrooms, as the logistics of granting remote access to a workstation or relying on the computational resources of each student is not trivia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Using pyDCA 25 as a python script in Jupyter Notebooks for execution in Google Colaboratory, 33 coevolutionary interactions were calculated using pseudo‐likelihood maximization direct coupling analysis (plmDCA) on MSAs generated using hmmalign from HMMER 32 . Two MSAs were analyzed: one with only nonredundant RfaH sequences from Interpro database ( Interpro , 1,005 sequences), and another one complemented with the sequences found in metaclust ( Interpro + MG , 5,379 sequences).…”
Section: Resultsmentioning
confidence: 99%
“…Using pyDCA 25 as a python script in Jupyter Notebooks for execution in Google Colaboratory, 33 coevolutionary interactions were calculated using pseudo‐likelihood maximization direct coupling analysis (plmDCA) on MSAs generated using hmmalign from HMMER 32 . Two MSAs were analyzed: one with only nonredundant RfaH sequences from Interpro database ( Interpro , 1,005 sequences), and another one complemented with the sequences found in metaclust ( Interpro + MG , 5,379 sequences).…”
Section: Resultsmentioning
confidence: 99%
“…Future work will include repeated teaching of EDirect for small molecule chemical information searching, along with a dedicated assessment component. Assessment could include, for example, quantitative measures of previous knowledge, understanding of the topics, student attitudes, and likelihood of continued use of the software tools and techniques …”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Assessment could include, for example, quantitative measures of previous knowledge, understanding of the topics, student attitudes, and likelihood of continued use of the software tools and techniques. 59 Additional future work will include writing a program to more closely integrate PUG-REST searches with EDirect. For example, in Figure 11, the first four lines use nquire to make a PUG-REST substructure search request, followed by xtract to obtain the list of compound identifiers, and then finally posting the compound identifiers to the Entrez server with epost.…”
Section: ■ Limitations and Future Workmentioning
confidence: 99%
“…16 All these implementations, however, leave some intermediate task to be performed or need to be set up on a cloud structure by the end user. An exception is described by Engelberger et al 17 which reported a collection of Jupyter notebooks for educational purposes that performs phylogenetic analysis, molecular modeling, molecular docking, molecular dynamics, and coevolutionary analysis. Although those protocols were not focused on MD calculations, they greatly inspired the present work.…”
Section: Introductionmentioning
confidence: 99%